Kepercayaan Mobile Banking: Peran Keamanan dan Kualitas Layanan Elektronik dalam Mendorong Niat Bertransaksi Ulang - Nissa, Hairun; Rosa, Aslamia; Maulana, Ahmad; Wahab, Zakaria (Al-Buhuts, 2024)
This study investigates the role of Security and Electronic Service Quality in influencing Repurchase Intention in the mobile banking application of Bank Sumsel Babel, with Trust as an intervening variable. Data collected from 131 respondents who actively use the mobile banking application were analyzed using Structural Equation Modeling (SEM) with Smart PLS 4. The results indicate that Electronic Service Quality significantly influences Repurchase Intention, both directly and indirectly through Trust as a mediator. Security, however, does not show a significant impact on Repurchase Intention, either directly or indirectly through Trust. Nonetheless, Security remains crucial in building initial Trust among users. This study provides insights for improving service quality and Security features to strengthen customer loyalty